A comparison of impact and risk assessment methods based on the IMO Guidelines and EU invasive alien species risk assessment frameworks - Greta Srėbalienė; Sergej Olenin; Dan Minchin; Aleksas Narščius (PeerJ, 2019)
A comparative analysis of two risk assessment (RA) frameworks developed to support the implementation of the international Ballast Water Management Convention (BWMC) and European Regulation on Invasive Alien Species (IAS) was performed. This analysis revealed both differences and similarities between the IMO Risk Assessment Guidelines (IMO, 2007) and EU Regulation supplement on RA of IAS (EU, 2018) in RA approaches, key principles, RA components and categories of IAS impacts recommended for assessment. The results of this analysis were used to produce a common procedure for the evaluation of the bioinvasion risk and impact assessment methods intended to support international, regional and/or national policy on IAS. The procedure includes a scoring scheme to assess compliance with the key principles, RA components and categories of bioinvasion impacts taken into account by the methods. In these methods the categories of impacts on human health and economy are underrepresented comparing with impacts on environment.